Differences in Manifestations and Gut Microbiota Composition Between Patients With Different Henoch-Schonlein Purpura Phenotypes - Zhang, Yuanzhen; Xia, Guizhi; Nie, Xiaojing; Zeng, Yugui; Chen, Yi; Qian, Yifang; Chen, Guangming; Huang, Jun; Wang, Chengfeng; Zhang, Chuanyin; Huang, Xiaoli; Yang, Yuen; et al. (Frontiers in Cellular and Infection Microbiology, 2021)
Background: Gut microbiota plays an important role in the pathogenesis of immune-mediated diseases. However, the complex pathogenesis of Henoch-Schonlein Purpura (HSP) remains elusive. This study aimed to characterize the gut microbiota in HSP patients and explore the potential association between gut microbiota composition and phenotypic changes in HSP. Methods: 16SrRNA gene sequencing and bioinformatic analyses were performed using total DNA extracted from the fecal microbiota of 34 children with HSP, including 18 primary cases, 16 recurrent cases, and 23 healthy children. Results: The diversity indexes showed significant differences in the microbial community among the primary HSP groups, the recurrent HSP group and healthy controls. The abundance of Escherichia-Shigella in the recurrent HSP group was significantly higher than that in the primary HSP group, and the constructed ROC curve had an AUC value of 0.750. According to the Spearman correlation analysis, the abundance of Bacteroides was positively associated with the serum IgG level in children with HSP, while the abundance of Lachnoclostridium was negatively correlated with the complement component 3 (C3). The diversity indexes of gut microbiota in the HSP group with abdominal symptoms were higher than those in the HSP group without GI involvement, and also higher than those in the healthy control group. In the HSP group with GI involvement, the abundance of Faecalibacterium was decreased, while the abundance of Streptococcus and Fusobacteria was increased, compared to the HSP group without GI involvement. Conclusions: The gut microbiota of children with HSP was different from that of healthy children. The genus Escherichia-Shigella has a diagnostic value for HSP recurrence. Bacteroides and Lachnoclostridium may affect IgG and complement C3 levels in children with HSP. Abdominal symptoms in HSP children were related to gut microbiota (Streptococcus and butyric acid-producing bacteria).